การจัดสรรเส้นทางและความยาวคลื่นในโครงข่ายใยแก้วนำแสงแบบหลายความยาวคลื่นที่มีโครงสร้างเป็นรูปวงแหวน 1 วง และแบบวงแหวนหลายวง - ศิริชัย อารีวานิช (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This thesis presents routing and wavelength allocation techniques in multi-wavelength single-ring and multi-ring networks. For routing and wavelength allocation in single-ring network, mathematical model formulations based on the integer linear programming (ILP) are used to determine the network costs which are measured in terms of the number of wavelengths required for supporting a given traffic demand. It is shown that the proposed mathematical models offer optimal solution but the computational time becomes a problem for a network larger than 16 nodes. In addition, a study on the effect of having wavelength conversion in the system shows that the complexity of the network resource allocation is reduced. This is because wavelength allocation is no longer required. Based on the simulation results, it is found that the optimal resource allocation in the systems with wavelength conversion can be applied to ring networks of up to 185 nodes. For the multi-ring network design, mathematical model formulations based on integer linear programming (ILP) and heuristic schemes are proposed on the condition that the traffic between any node pair can be distributed to flow over more than one ring, but any portion of the traffic must be restricted to flow within only one ring. The mathematical model formulations for multi-ring network design can guarantee optimal solution. However, the computational time of the mathematical modeling appears to be excessive even with a network as small as 8 nodes with 13 links. Accordingly, heuristic algorithms that can solve large network problems are introduced. These algorithms cannot guarantee optimal solution but, in general, they can achieve near optimal results. These developed algorithms are then used to perform cost comparisons between the multi-ring and mesh design approaches. It appears that the multi-ring network design approach requires less than 17% additional costs in comparison to the mesh design counterpart. consequently, the multi-ring network design is considered suitableand effective for practical applications.